Photodynamic inactivation of planktonic and biofilm growing bacteria mediated by a meso-substituted porphyrin bearing four basic amino groups - Mamone, Leandro Ariel (2016)
Biofilm-associated diseases account for 80% of all infections in humans. Due to the emergence of antibiotic resistances, alternative therapies such as Photodynamic Inactivation (PDI) of microorganisms have emerged. Porphyrins with intrinsic positive charges have been proposed as successful photosensitizers (PSs) against microorganisms. We have recently designed the new synthetic porphyrin 5,10,15,20-tetrakis[4-(3-N,N-dimethylammoniumpropoxy)phenyl]porphyrin (TAPP) containing four basic amine groups in the periphery of the tetrapyrrolic macrocycle, which can acquire positive charges at physiological pH, thus favouring the interaction with biomembranes. Illumination of planktonic cultures of Staphylococcus aureus at 180 J/cm2 in the presence of 2.5 μM TAPP induced complete bacteria eradication. For the TAPP-PDI treatment of S. aureus biofilms, higher light fluences and PS concentrations were needed. Employing 20 μM TAPP and 180 J/cm2, around 3-log CFU reduction were obtained. In order to determine the efficacy of TAPP-PDI on Gram-negative bacteria, we performed planktonic and biofilm assays employing Pseudomonas aeruginosa. Much higher TAPP doses as compared to S. aureus were needed to achieve planktonic bacteria photosensitization (3-log CFU reduction at 20 μM TAPP and 180 J/cm2). On the other hand, high concentrations of TAPP were nontoxic to P. aeruginosa growing on biofilms, and employing 30 μM TAPP and 180 J/cm2 we obtained 3-log CFU reduction. The main conclusion of the present work is that TAPP is a promising and efficient PS capable of promoting photodynamic killing of both Gram-negative and -positive in planktonic bacteria, though more effectively in the latter. In addition, TAPP-PDI induces similar photoinactivation rates in both bacteria types growing on biofilms, with lower dark toxicity in the Gram-negative one.